1996
DOI: 10.1103/physrevb.53.2835
|View full text |Cite
|
Sign up to set email alerts
|

Influence of twin boundaries on Josephson junctions between high-temperature and conventional superconductors

Abstract: We give a consistent explanation of the c-axis Josephson tunneling experiment by Sun and co-workers between YBa 2 Cu 3 O 6ϩx and Pb within the d-wave pairing scenario. Using a Ginzburg-Landau formulation, orthorhombic deformation and twinning of the crystal lattice are taken into account. In the presence of orthorhombic distortion, symmetry arguments allow a c-axis Josephson coupling between YBa 2 Cu 3 O 6ϩx and Pb. However, for a highly twinned YBa 2 Cu 3 O 6ϩx sample, the Josephson coupling is weakened due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 37 publications
2
82
0
Order By: Relevance
“…There is a staggered phase for the d x 2 −y 2 -component. This would give rise to compensating contributions of the two domains to the Josephson effect, similar to the situation discussed in the context of c-axis junction between an s-wave and a twinned hightemperature superconductor 38,39 . In addition, this configuration could give rise to spontaneous half-quanta flux lines wherever a domain wall hits the junction perpendicularly.…”
Section: Other Chiral Superconducting Phasesmentioning
confidence: 95%
“…There is a staggered phase for the d x 2 −y 2 -component. This would give rise to compensating contributions of the two domains to the Josephson effect, similar to the situation discussed in the context of c-axis junction between an s-wave and a twinned hightemperature superconductor 38,39 . In addition, this configuration could give rise to spontaneous half-quanta flux lines wherever a domain wall hits the junction perpendicularly.…”
Section: Other Chiral Superconducting Phasesmentioning
confidence: 95%
“…(i) Sigrist et al have suggested that the phase of the s-wave component in YBCO does not simply jump from 0 to π upon crossing the twin boundary, but rather changes in a smooth way, attaining the value of π/2 right at the twin boundary [7]. The twinned YBCO sample is thus assumed to exhibit a macroscopic d + is pairing symmetry.…”
mentioning
confidence: 99%
“…However, YBCO has orthorhombic symmetry which implies that the order parameter cannot be purely d-wave and must contain an additional s-wave contribution [9][10][11][12][13]. This has significant consequences for c-axis Josephson tunneling experiments between YBCO and Pb (a standard s-wave superconductor).…”
Section: 20mn7425btmentioning
confidence: 99%
“…The relative phase α is fixed by the bulk free energy of YBCO and is 0 for one type of twin domain and π for the other [10,11]. The intrinsic phase shift of the junction is determined by α.…”
Section: 20mn7425btmentioning
confidence: 99%